2022
DOI: 10.3390/biom12101357
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy in Osteoarthritic Cartilage

Abstract: Osteoarthritis (OA) is one of the most common diseases leading to physical disability, with age being the main risk factor, and degeneration of articular cartilage is the main focus for the pathogenesis of OA. Autophagy is a crucial intracellular homeostasis system recycling flawed macromolecules and cellular organelles to sustain the metabolism of cells. Growing evidences have revealed that autophagy is chondroprotective by regulating apoptosis and repairing the function of damaged chondrocytes. Then, OA is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 150 publications
0
14
0
Order By: Relevance
“…With more in-depth understanding of osteoarthritis, its complex etiology and the interaction of internal and external structures in joints have become the focus of scientists’ attention. As the largest and most complex joint in the human body, the knee joint, articular cartilage, subchondral bone, synovium, infrapatellar fat pad, ligaments, and skeletal muscles jointly promote or inhibit the progression of osteoarthritis [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…With more in-depth understanding of osteoarthritis, its complex etiology and the interaction of internal and external structures in joints have become the focus of scientists’ attention. As the largest and most complex joint in the human body, the knee joint, articular cartilage, subchondral bone, synovium, infrapatellar fat pad, ligaments, and skeletal muscles jointly promote or inhibit the progression of osteoarthritis [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is activated as an adaptive response to sublethal conditions, with the aim to avoid cell death ( Klionsky, 2005 ; Levine & Yuan, 2005 ). Some studies have found that the ULK1, beclin-1, LC3 protein expression is decreased in the superficial zone, while these proteins are strongly expressed in the middle and deep zone ( Kao et al, 2022 ). In later stages, there is an all-layered autophagic genetic change, including not only reduced ULK1, LC3, and beclin-1 but also fewer ATG3, ATG5, and ATG12.…”
Section: Role and Potential Mechanism Of Chondrocyte Autophagy In Ost...mentioning
confidence: 99%
“…Targeted deletion of ATG in chondrocytes can promote cell death ( Vuppalapati et al, 2015 ). Furthermore, the loss of proteoglycan is associated with reduced autophagic markers in OA ( Kao et al, 2022 ). As essential organelles in chondrocytes, mitochondria supply energy and play vital roles in cellular metabolism and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Knee osteoarthritis (KOA) is the most prevalent form of arthritis characterized by a degeneration of articular cartilage resulting in the development of osteophytes, or bone spurs ( Horecka et al, 2022 ). The global prevalence of KOA is around 3.8% ( Kao et al, 2022 ). KOA is closely associated with age, as radiographic evidence of KOA occurs in most people over the age of 65 years ( Lespasio et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%